Fear of COVID and Trait Anxiety: Mediation of Resilience in University Students - Gonçalves, Marina Pereira (2021)
The current research aimed to assess the effect of the trait anxiety on fear of Covid-19 mediated by resilience. For that, we counted on a convenience sample of 261 university students from Brazil. Participants completed a survey composed by the Fear of Covid-19 Scale (FC-19S), the Brief Resilience Scale, the Trait Anxiety Inventory, and demographic questions. Results from a simple mediation with 5000 bootstrap simulations supported the hypothesis that resilience mediates the link between the trait anxiety and fear of Covid-19 (β = .14; 95% C.I. = .027, .254). It was observed that resilience mediated around 35% of the link between the trait anxiety and fear of Covid-19. In sum, we concluded that resilience shows an important role for the maintenance of people’s mental health, which is especially relevant in troubled times like the pandemic.